Correction of narrow nostril deformity secondary to cleft lip: indications for different surgical methods and a retrospective study - Wei, Hongpu; Xu, Xiaofeng; Wan, Teng; Yang, Yusheng; Zhang, Yong; Wu, Yilai; Liang, Yun (Frontiers in Pediatrics, 2023)
Background: Cleft lip and/or palate (CLP) can lead to severe nasolabial deformities that significantly affect the appearance of the patient. Among all types of nasolabial deformities, narrow nostril deformities are the most troublesome, causing poor and unstable surgical outcomes. The purpose of this study was to develop an algorithm for surgical method selection for revision of narrow nostril deformities secondary to CLP based on retrospective clinical data. Materials and Methods: Patients with narrow nostril deformities secondary to CLP were enrolled in the study. Before surgery, patients’ clinical data were collected and the width of the nasal floor and the length of the alar rim were measured. Surgical methods were determined according to the measurements. After surgery, a nostril retainer was applied for 6 months to consolidate and maintain the nostril shape. The surgical method and postsurgical changes were recorded for the final summary of the algorithm to select surgical methods for narrow nostril deformities. Results: The data from 9 patients were analyzed. According to the width of the nasal floor and the length of the alar rim, correct surgical methods were determined. Four patients received nasolabial skin flaps to widen the soft tissue of the nasal floor. Three patients received upper lip scar tissue flaps to treat the narrow nasal floor. For the short alar rim, free alar composite tissue flap or narrowing of the nostril of the noncleft side was recommended. Conclusion: The width of the nasal floor and the length of the alar rim are critical elements to consider when selecting the correct surgical method for revising narrow nostril deformities secondary to CLP. The proposed algorithm provides a reference for selecting surgical methods in future clinical practice.